2014
DOI: 10.5132/eec.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and genotoxic effects of a commercial formulation of the herbicide tebuthiuron in Oreochromis niloticus of different sizes

Abstract: Pesticides are serious contaminants because they are designed to eliminate pests, but they also affect non-target species. The present study aimed to evaluate the biochemical and genetic effects of the herbicide tebuthiuron in Oreochromis niloticus of different sizes. Thus, we analyzed biomarkers in small and large O. niloticus specimens exposed to 62.5, 125 and 250 mg L-1 of tebuthiuron for 72 hours. Fish exposed to 250 mg L-1 had high mortality rates; therefore, the data could not be used. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
2
4
0
1
Order By: Relevance
“…Previous studies by our group (Franco-Bernardes et al, 2014) showed similar data for Nile Tilapia exposed to the herbicide tebuthiuron, and so did a study by Kanak et al (2014), in which the authors exposed this species to metal using antioxidant parameters. Both studies revealed greater responsiveness in small fish, corroborating the results of our work.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies by our group (Franco-Bernardes et al, 2014) showed similar data for Nile Tilapia exposed to the herbicide tebuthiuron, and so did a study by Kanak et al (2014), in which the authors exposed this species to metal using antioxidant parameters. Both studies revealed greater responsiveness in small fish, corroborating the results of our work.…”
Section: Discussionsupporting
confidence: 59%
“…Similar kinds of results were also seen by some other researchers [10]. None of the sub-lethal exposure days -24 h, 7 d, 14 d and 21 d showed the formation of micronuclei.…”
Section: Discussionsupporting
confidence: 78%
“…This molecule [1-(5-tert-butyl-1,3,4-thiadiazol-2-yl)-1,3dimethylurea] has a systemic action and acts in the inhibition of photosystem II (Breitenbach et al, 2001). However, tebuthiuron can cause environmental damage since it is considered dangerous to the environment due to its high persistence and long half-life in the environment, moderate to extreme toxicity (Rodrigues and Almeida, 2011), low sorting capacity in soil (Koskinen et al, 1996), and high solubility in water (Franco-Bernardes et al, 2014). Hence, residual concentration is an extremely important factor, as it results in a greater potential for contamination.…”
Section: Introductionmentioning
confidence: 99%